PENGARUH KEPUASAN KERJA DAN KOMITMEN PEGAWAI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PEGAWAI STRUKTURAL IAIN PADANGSIDIMPUAN - LUBIS, ASWADI (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
Good behaviour is needed to support the organization, it is as the based problem in this research. The employees not only should have good skills but also good behaviours, known as extra skills. In order to know further about it, the researcher examined the effect of job satisfaction and employee commitment on Organizational Citizenship Behavior (OCB). The samples were all employees of the structural IAIN Padangsidimpuan that civil servants who numbered 53 employees. Data collection techniques used to obtain data on job satisfaction, employee commitment and Organizational Citizenship Behavior (OCB) is a questionnaire. While testing the hypothesis used multiple regression analyzes with SPSS 22. The results showed that job satisfaction to the employees of the State Islamic Institute Padangsidimpuan have a significant influence on Citizenshif Organizational Behavior (OCB) based on employee perceptions. From the analysis, the result that job satisfaction and Organizational Commitment to give effect to Citizenshif Organizational Behavior (OCB) in institutions. Job Satisfaction and Organizational Commitment influence simultaneously against Citizenshif Organizational Behavior (OCB). This is evidenced by the simultaneous test (F test) and test the coefficient of determination that is equal to 83% Citizenshif Organizational Behavior (OCB) is influenced by variations in two variables used in the study, the rest is another factor. Job satisfaction is more dominant influence on Citizenshif Organizational Behavior (OCB). This is evidenced by the regression coefficient greater job satisfaction than organizational commitment based on the study the researchers did on the institution Padangsidimpuan State Islamic Institute